Colonic Tuberculosis and Chronic Diarrhea - Tommy P Sibuea; Ari Fahrial Syam; Vera D Yoewono; Marcellus Simadibrata (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2001)
We describe that often colonic tuberculosis remains unsuspected prior to surgery. We therefore draw attention to pitfalls in the diagnosis and review the literature on the diagnostic modalities available to diagnose the disease. Today, the prompt diagnosis of an unknown gastroenteritis process involves colonoscopy. Using a fiberscope, a procedure with instantaneous return can be carried out. Patients with clinical presentation suggestive of colonic tuberculosis should have had either an aggressive diagnostic work out using high-yield tests or anti tuberculosis therapy.  Key words: Colonic tuberculosis, chronic diarrhea, colonoscopy